2008
DOI: 10.1136/qshc.2006.021873
|View full text |Cite
|
Sign up to set email alerts
|

Patient-actor perception of care: a comparison of obstetric emergency training using manikins and patient-actors

Abstract: All multiprofessional training improved patient-actor perception of care. Training using a patient-actor may be better at improving perception of safety and communication than training with a computerised manikin simulator.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
102
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(105 citation statements)
references
References 17 publications
0
102
0
3
Order By: Relevance
“…5 Other studies have confirmed construct validity of the PPS in simulation. 6,22 Of course, communication, safety and respect are not the only factors associated with maternal satisfaction.…”
Section: Introductionmentioning
confidence: 88%
“…5 Other studies have confirmed construct validity of the PPS in simulation. 6,22 Of course, communication, safety and respect are not the only factors associated with maternal satisfaction.…”
Section: Introductionmentioning
confidence: 88%
“…Ten of the papers were related to the Simulation and Fire-drill Evaluation (SaFE) study and were treated as one intervention [19][20][21][22][23][24][25][26][27][28]. Two articles reporting on the Programa de Rescate Obstétrico y Neonatal: Tratamiento Óptimo y Oportuno (PRONTO) trial were included (the pilot study and some of the first results pertaining to changes after the second training module) [29,30].…”
Section: Synopsis Of Peer-reviewed Articles Included In the Reviewmentioning
confidence: 99%
“…Thirteen studies had been conducted in [19][20][21][22][23][24][25][26][27][28] 6 DH (L2&L3) -HIC 10 RCT 2a,b,c 3b NHS Foundation Trust, Liverpool, UK [44,45] --HIC 1 Before-after 4b,c Victoria, Australia [46] 7 [48] --LMIC 1 Before-after 1 2b −−− −−− Sub-Saharan Africa (7 countries) [49] --LMIC 1 Before-after 1 2b,c −−− −−− Somaliland, Somalia [50] 3 8 LMIC 1 Before-after 1 2b,c 3a 4b Making it Happen, Bangladesh & India [52] 4 DH (Bangl.) [54] 3 DH; 3 FH 40 LMIC 1 Quasi-experimental 3c CRM based National study, US [58] 15 -HIC 1 RCT 4c Beth Israel Deaconness Medical Center, US [59] 1 TTH -HIC 1 Before-after 2a 4b,c Perinatal Safety Initiative, US [60] 1 TH -HIC 1 Before-after 3a 4b,c Rhode Island Hospital, US [61] 1 -HIC 1 Before-after 4b,c Geneva University Hospital, Switzerland [63] 1 TTH -HIC 1 Before-after 1 2a 3a TeamSTEPPS, US [18] 3 CH -HIC 1 RCT 2a 4c OBCTT, Southeast US [62] 1 TTH -HIC 1 Quasi-experimental before-after 1 2a,b,c −−− −−− OTHER CEmONC, Tanzania [17] 1 DH LMIC 1 Before-after 3c Copenhagen University Hospital, Denmark [64] 1 TTH -HIC 1 Before-after 1 2a,b 3a 4b University of Oporto, Portugal [65] 1 TTH -HIC 1 Before-after 1 2b 3a * In progress -abstracts not included [31,32] DH = district hospital L1 = level 1 −−− = studies not going beyond Kirkpatrick level 2 RH = referral hospital L2 = level 2 (secondary/regional) FH = field hospital TH = tertiary hospital/medical centre L3 = level 3 (tertiary) CH = community hospital TTH = tertiary and teaching hospital included in the studies spans the whole spectrum from tertiary teaching hospitals to community-and field hospitals.…”
Section: Synopsis Of Peer-reviewed Articles Included In the Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Whatever the method, the core aims are to progress training, to improve clinical outcomes and to enhance the patient experience. 1,2 Other benefits might include improved recruitment to our speciality, 3 greater satisfaction with training, better teamworking 4 and professional attitudes to safety. 5 Moreover, as well as being a tool to enhance professional development, medical simulation might prove to be a means of formal assessment of skills for certification and revalidation.…”
Section: Introductionmentioning
confidence: 99%